If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + -12 = 13 + x Reorder the terms: -12 + -4x = 13 + x Solving -12 + -4x = 13 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -12 + -4x + -1x = 13 + x + -1x Combine like terms: -4x + -1x = -5x -12 + -5x = 13 + x + -1x Combine like terms: x + -1x = 0 -12 + -5x = 13 + 0 -12 + -5x = 13 Add '12' to each side of the equation. -12 + 12 + -5x = 13 + 12 Combine like terms: -12 + 12 = 0 0 + -5x = 13 + 12 -5x = 13 + 12 Combine like terms: 13 + 12 = 25 -5x = 25 Divide each side by '-5'. x = -5 Simplifying x = -5
| 5m+8-2m=17+4m-3 | | 5y=x+17 | | 6m-12m=1-4 | | 40x+780=70x+1230 | | 8y-6(3y-7)=0 | | 81^-3/4 | | 20x+800=50x+1250 | | 20x+80=50x+1250 | | 6m-12m=-3 | | 12-(1/9)d=17 | | -x/3+9=1x+21 | | 3n/4-8=0 | | .6a+2=.3+4+4+4+4+1 | | 40x+80=70x+125 | | x(x-14)=-7(4x+7) | | 47+3y-21=12y-9-4y | | 4/3n=36 | | 9x^2-36x+29=0 | | 40x+800=70x+1250 | | 7c-8+3(c-9)=-75 | | 6x^2-12x-11=0 | | (x+7)(3x+4)=-14 | | 5-3x=12-6x | | 7x+1=(4x+4) | | 14-9y=-13 | | 2/7k-1/14=-3 | | 459=16x+7 | | 3x(3x+2)=35 | | m-61/4=93/8 | | u^2-9/169 | | -3/7p=36 | | y-4=5/4(x+8) |